2019
DOI: 10.18632/oncotarget.27320
|View full text |Cite
|
Sign up to set email alerts
|

Targeted enhancement of the therapeutic window of L19-TNF by transient and selective inhibition of RIPK1-signaling cascade

Abstract: IntroductionCytokine-based products are gaining importance for cancer immunotherapy. L19-TNF is a clinical-stage antibody-cytokine fusion protein that selectively accumulates to tumors and displays potent anticancer activity in preclinical models. Here, we describe an innovative approach to transiently inhibit off-target toxicity of L19-TNF, while maintaining antitumor activity.MethodsGSK’963, a potent small molecule inhibitor of RIPK1, was tested in tumor-bearing mice for its ability to reduce acute toxicity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…CSG targeting of TNFα is critical to induce vessel dilation and improve tumour perfusion [49]. This outcome is different from the anti-vascular effect of TNFα, where TNFα-targeted peptides bind to tumour blood vessels or ECM proteins that are primarily located around tumour blood vessels [29,65,66]. Whilst we are interested in developing TNFα-CSG as an anti-cancer therapeutic, as an imaging agent, CSG-IO-NP may be used for diagnostic screening to identify patients who may benefit from TNFα-CSG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CSG targeting of TNFα is critical to induce vessel dilation and improve tumour perfusion [49]. This outcome is different from the anti-vascular effect of TNFα, where TNFα-targeted peptides bind to tumour blood vessels or ECM proteins that are primarily located around tumour blood vessels [29,65,66]. Whilst we are interested in developing TNFα-CSG as an anti-cancer therapeutic, as an imaging agent, CSG-IO-NP may be used for diagnostic screening to identify patients who may benefit from TNFα-CSG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that therapeutic index and anti-cancer activity of potent cytokines such as IL-2 [ 11 , 15 ], IL-12 [ 39 ] or TNF [ 12 , 40 ], can be improved by fusing them to the L19 antibody in various formats. In this study, the therapeutic activity and tolerability of the parental L19-TNF WT was directly compared to the L19-TNF I97A mutant in a syngeneic mice model study.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the single point mutation I97A (located at the interface between TNF subunits) reduced the binding affinity of TNF to its cognate receptor TNFR1, resulting in an approximately 50-fold faster dissociation rate when compared to the wild type protein ( Figure 4 ). The I97A mutation enabled dose escalation of the immunocytokine beyond the previously established MTD (i.e., 375 μg/Kg), with non-detectable toxicity in a preclinical model of cancer [ 40 ]. In contrast, the respective wild type TNF fusion protein showed lower tolerability when administered at an equimolar dose in the same tumor model ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, small molecule inhibitors have been used to temporarily inhibit the respective signaling pathway of the cytokine receptor [ 147 ]. This attenuates payload-mediated toxicity in the circulation.…”
Section: Current Challenges and Routes Of Future Payload Developmentmentioning
confidence: 99%